The Influence of PEG400 and Acetone on Polysulfone Membrane Morphology and Fouling Behaviour - P.T.P. Aryanti; Shelli R. Joscarita; Anita K. Wardani; S. Subagjo; Danu Ariono; I Gede Wenten (Journal of Engineering and Technological Sciences, 2016)
Modification of polysulfone ultrafiltration membrane was conducted by blending polysulfone with PEG400 and acetone as additives. The influence of each additive on the resulted membrane morphology and fouling characteristics were investigated. The experimental results showed that the hydrophilicity of the polysulfone membrane was improved by the increase of PEG400 in the polysulfone membrane. The water contact angle of the membrane was decreased from 76.1° to 38.31° when 35 %wt of PEG400 was added into the polysulfone solution, while the water content of the membrane was increased by around 38%. The high concentration of PEG400 in the polysulfone solution led to the formation of longer finger-like cavities in the membrane structure and resulted in a thicker membrane skin layer. The high concentration of PEG400 also contributed to the increase in hydraulic resistance of the membrane due to organic matter fouling. This problem could be minimized by the addition of acetone into the polysulfone solution, which resulted in a lower fouling resistance of organic matter during up to five hours of peat water filtration.